DISTINCTIVE COLLECTIVIST IDENTITY ON DIGITAL ADS: HARI RAYA AND LEBARAN 2021 - Marta, Rustono Farady; Supina, Supina; Rashid, Sabrina Mohd; Karolina, Cut Meutia; Naseer, Moazzam (Master of Communication Science Program, Universitas Diponegoro, 2022)
Every family has a particular moment, especially in Malaysia and Indonesia, where the majority of the population is Muslim, where Eid al-Fitr has established a tradition for bringing family members closer together. Simply said, the tradition is known as